Sodium ion single crystal oxide positive electrode material, battery and vehicle

By sintering the polycrystalline oxide with sodium carbonate and ammonium bicarbonate after ball milling, a sodium ion single crystal oxide positive electrode material was prepared, which solved the problem of cracks caused by particle shrinkage and expansion during the circulation process of the polycrystalline oxide positive electrode material, and significantly improved the circulation performance and capacity retention rate of the sodium ion battery.

CN119330422BActive Publication Date: 2025-04-15ZHEJIANG HUAYU NADIAN NEW ENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411874701.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2024-12-02
Filing Date
2024-12-19
Publication Date
2025-04-15
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The positive electrode materials of existing sodium ion batteries are mostly polycrystalline oxides. During the cycle, cracks are formed due to the shrinkage and expansion of particles, resulting in increased impedance and loss of capacity. The material has poor performance and low tap density.

Method used

The polycrystalline oxide after ball milling is sintered with sodium carbonate and ammonium bicarbonate to prepare a sodium ion single crystal oxide positive electrode material, and the circulation stability and capacity retention rate of the material are improved through dual gas modification.

Benefits of technology

It significantly improves the circulation performance, rate performance and capacity retention rate of sodium ion batteries, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330422B_ABST
    Figure CN119330422B_ABST
Patent Text Reader

Abstract

The present invention discloses a sodium ion single crystal oxide positive electrode material, a battery and a vehicle, and belongs to the technical field of sodium ion batteries, and specifically relates to a method for preparing a sodium ion single crystal oxide positive electrode material, comprising: firstly ball milling a polycrystalline oxide positive electrode material, then mixing it with sodium carbonate and sintering it, and finally mixing it with ammonium bicarbonate and sintering it to obtain a sodium ion single crystal oxide positive electrode material; the mass ratio of the amount of sodium carbonate used to the amount of the polycrystalline oxide positive electrode material used is 0.5:1-2:1; the mass ratio of the amount of ammonium bicarbonate used to the amount of the polycrystalline oxide positive electrode material used is 0.1:1-0.5:1. The present invention also discloses a sodium ion positive electrode sheet and a sodium ion battery made of the sodium ion single crystal oxide positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a sodium ion single crystal oxide positive electrode material, a battery and a vehicle. Background Art

[0002] Sodium-ion batteries have the advantages of abundant raw materials, excellent low-temperature performance, and high safety, and have received widespread attention in recent years. However, there are still some obstacles on the road to the long-term development of sodium-ion batteries, such as high cost, low specific energy density, and poor cycle performance. At present, the cost and specific energy density of sodium-ion batteries are directly linked to the performance of the positive electrode material. Oxide ternary materials have attracted widespread attention due to their high reversible capacity, good rate performance, and low cost, and have become the first choice for positive electrode materials for sodium-ion batteries. Oxide ternary positive electrode materials are mostly polycrystalline secondary spherical particles, which will form cracks at the grain boundaries during the cycle due to the anisotropic shrinkage / expansion of the primary particles. As the cycle proceeds, the electrolyte will penetrate these cracks, causing the formation of a disordered cationic phase along the cracks inside the particles, resulting in an increase in impedance. Eventually, the secondary particles are broken, resulting in an irreversible loss of capacity. In addition, the polycrystalline oxide positive electrode materials currently used have a large particle size, poor material rate capability, and low tap density.

[0003] Most of the existing oxide positive electrode materials are polycrystalline particles. During the cycle, cracks will form at the grain boundaries due to the anisotropic contraction / expansion of the primary particles. As the cycle progresses, the electrolyte will penetrate these cracks, causing the cationic disordered phase to form along the cracks inside the particles, resulting in increased impedance. In addition, during the cycle, interfacial reactions will occur between the positive electrode material particles and the electrolyte, affecting the capacity and cycle performance of the battery; the larger particle size of the polycrystalline material makes the material's rate performance poor; the polycrystalline material has a low tap density, which affects the energy density of the battery cell. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a sodium ion single crystal oxide positive electrode material having high capacity retention rate and good cycle performance after being made into a battery.

[0005] An object of the present invention is to provide a modification method for preparing a sodium ion battery oxide positive electrode material with excellent cycle performance.

[0006] Another object of the present invention is to provide such a positive electrode material for use as a positive electrode material for a sodium ion battery, which can significantly improve the cycle performance and capacity of the battery cell.

[0007] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:

[0008] A method for preparing a sodium ion single crystal oxide positive electrode material comprises: firstly ball-milling a polycrystalline oxide positive electrode material, then mixing it with sodium carbonate and sintering it, and finally mixing it with ammonium bicarbonate and sintering it to obtain a sodium ion single crystal oxide positive electrode material; the mass ratio of the amount of sodium carbonate used to the amount of the polycrystalline oxide positive electrode material used is 0.5:1~2:1; the mass ratio of the amount of ammonium bicarbonate used to the amount of the polycrystalline oxide positive electrode material used is 0.1:1~0.5:1. After the polycrystalline oxide positive electrode material is made into a sodium ion battery positive electrode material, cracks will be formed at the grain boundary during the cycle process due to the anisotropic contraction / expansion of the polycrystalline oxide positive electrode material particles, resulting in a decrease in the performance of the manufactured battery. The present invention successively adopts sodium carbonate sintering treatment and ammonium bicarbonate sintering treatment to obtain a sodium ion single crystal oxide positive electrode material. During the sintering treatment of ammonium bicarbonate, the ammonium bicarbonate decomposes to produce CO 2 and NH 3 , CO 2 and NH 3 The dual-gas modification of the sodium-ion single-crystal oxide positive electrode material can protect the obtained sodium-ion single-crystal oxide positive electrode material, reduce the formation of cracks due to anisotropic shrinkage / expansion during the cycle process, and improve the rate performance, cycle stability and capacity retention rate of the prepared sodium-ion battery.

[0009] Preferably, in the ball milling treatment, zirconia ball milling beads are used for ball milling, and the ball-to-material ratio of zirconia ball milling beads to polycrystalline oxide positive electrode material is 15:1 to 20:1; or, the polycrystalline oxide positive electrode material is NaNi x Fe y Mn z O 2 , x+y+z=1, 0.2≤x<0.6, 0.2≤y<0.6.

[0010] Preferably, in the sintering treatment after mixing with sodium carbonate, the sintering is carried out at 700-900° C. in an oxygen atmosphere for 8-16 hours; or, in the sintering treatment after mixing with ammonium bicarbonate, the sintering is carried out at 600-850° C. in an argon atmosphere for 8-12 hours.

[0011] Preferably, in the preparation of the sodium ion single crystal oxide positive electrode material, the zirconium oxide ball milling beads and the polycrystalline oxide positive electrode material are put into a zirconium oxide ball milling jar, ball milled at a speed of 400-600 r / min for 0.5h-3h, washed with water, filtered, and dried to obtain an intermediate product 1, the intermediate product 1 is mixed with sodium carbonate, sintered at 700-900°C for 8-16h in an oxygen atmosphere, washed with water after cooling, filtered, and dried to obtain an intermediate product 2, the intermediate product 2 is mixed with ammonium bicarbonate, sintered at 600-850°C for 8-12h in an argon atmosphere, washed with water after cooling, filtered, and dried to obtain a sodium ion single crystal oxide positive electrode material.

[0012] More preferably, in the preparation of the sodium ion single crystal oxide positive electrode material, the polycrystalline oxide positive electrode material is NaNi x Fe y Mn z O 2 , x+y+z=1, 0.2≤x<0.6, 0.2≤y<0.6.

[0013] More preferably, in the preparation of the sodium ion single crystal oxide positive electrode material, the ball-to-material ratio of zirconium oxide ball milling beads to polycrystalline oxide positive electrode material is 15:1 to 20:1.

[0014] More preferably, in the preparation of the sodium ion single crystal oxide positive electrode material, the amount of the intermediate product 1 is measured based on the polycrystalline oxide positive electrode material, and the mass ratio of the amount of sodium carbonate used to the amount of the polycrystalline oxide positive electrode material used is 0.5:1~2:1.

[0015] More preferably, in the preparation of the sodium ion single crystal oxide positive electrode material, the amount of the intermediate product 2 is measured based on the polycrystalline oxide positive electrode material, and the mass ratio of the amount of ammonium bicarbonate used to the amount of the polycrystalline oxide positive electrode material used is 0.1:1 to 0.5:1.

[0016] The invention discloses a sodium ion single crystal oxide positive electrode material prepared by the method.

[0017] The invention discloses a method for preparing a sodium ion battery, comprising: the above-mentioned sodium ion single crystal oxide positive electrode material.

[0018] Preferably, the sodium ion single crystal oxide positive electrode material and the binder are mixed in a solvent, and after homogenization, the positive electrode plate of the sodium ion battery is prepared; then, the positive electrode plate of the sodium ion battery is assembled with the negative electrode plate of the sodium ion battery, the separator and the electrolyte to prepare the sodium ion battery; the binder comprises a mixture of one or more of PVDF, sodium lignin sulfonate and sodium lignin sulfonate derivatives, and the sodium lignin sulfonate derivatives have ethoxyethoxyethyl acrylate groups and diethyl chloromalonate groups. When the present invention uses the sodium ion single crystal oxide positive electrode material modified by double gas to prepare the positive electrode plate of the sodium ion battery, the sodium lignin sulfonate derivative obtained by modifying the sodium lignin sulfonate with ethoxyethoxyethyl acrylate and diethyl chloromalonate can also be used. After the sodium ion battery is prepared by using the above-mentioned sodium ion single crystal oxide positive electrode material and the sodium lignin sulfonate derivative together, the performance of the sodium ion battery such as rate performance, cycle stability and capacity retention rate can be improved.

[0019] More preferably, the solvent is NMP; or, the amount of the sodium ion single crystal oxide positive electrode material used is 30-50wt% of the solvent; or, the amount of the binder used is 5-15wt% of the sodium ion single crystal oxide positive electrode material.

[0020] More preferably, the binder is a sodium lignin sulfonate derivative having an ethoxyethoxyethyl acrylate group and a diethyl chloromalonate group.

[0021] Preferably, in the preparation of the sodium ion battery, the binder and the sodium ion single crystal oxide positive electrode material are added to NMP and mixed, and the mixture is homogenized at 800-1200 rpm for 10-60 min to obtain a positive electrode slurry, and then a positive electrode sheet is made; the hard carbon material, carboxymethyl cellulose, and acetylene black are mixed, and the mixture is homogenized at 800-1200 rpm for 10-60 min to obtain a negative electrode slurry, and then a negative electrode sheet is made; a polypropylene diaphragm is used as a diaphragm, and the above-mentioned positive electrode sheet, negative electrode sheet and electrolyte are assembled into a button half-cell.

[0022] More preferably, in the preparation of the sodium ion battery, the amount of the sodium ion single crystal oxide positive electrode material used is 30-50wt% of NMP.

[0023] More preferably, in the preparation of the sodium ion battery, the binder is one or more of PVDF, sodium lignin sulfonate and sodium lignin sulfonate derivatives, and the amount of the binder used is 5-15wt% of the sodium ion single crystal oxide positive electrode material.

[0024] More preferably, in the preparation of the sodium ion battery, the sodium ion single crystal oxide positive electrode material loading on the positive electrode sheet is 10-60 mg cm -2 .

[0025] More preferably, in the preparation of sodium ion batteries, the amount of carboxymethyl cellulose used is 2-10wt% of the hard carbon material.

[0026] More preferably, in the preparation of the sodium ion battery, the amount of acetylene black used is 2-10wt% of the hard carbon material.

[0027] More preferably, in the preparation of the sodium ion battery, the hard carbon material loading on the negative electrode sheet is 10-60 mg cm -2 .

[0028] More preferably, in the preparation of the sodium ion battery, the electrolyte is NaPF 6 Solution, electrolyte is NaPF 6 , ethylene carbonate and diethyl carbonate, the electrolyte contains NaPF 6 The concentration is 0.5-2M, and ethylene carbonate and diethyl carbonate are mixed in the electrolyte in a volume ratio of 1:0.5-2.

[0029] Preferably, the preparation of the sodium ion battery also includes the preparation of grafted sodium lignin sulfonate and the preparation of sodium lignin sulfonate derivatives.

[0030] More preferably, in the preparation of grafted sodium lignin sulfonate, sodium lignin sulfonate is added to deionized water and mixed to obtain a sodium lignin sulfonate solution, potassium persulfate is added and mixed at 40-60° C. under an inert gas atmosphere, and then ethoxyethoxyethyl acrylate is added at 60-90° C. to react for 1-2 hours. After the reaction is completed, isopropanol is added, the mixture is allowed to stand to precipitate, filtered and separated, and dried to obtain grafted sodium lignin sulfonate.

[0031] More preferably, in the preparation of grafted sodium lignin sulfonate, the amount of sodium lignin sulfonate used is 5-25 wt % of deionized water.

[0032] More preferably, in the preparation of grafted sodium lignin sulfonate, the amount of potassium persulfate used is 1-8 wt % of the sodium lignin sulfonate.

[0033] More preferably, in the preparation of grafted sodium lignin sulfonate, the amount of ethoxyethoxyethyl acrylate used is 5-20wt% of the sodium lignin sulfonate.

[0034] More preferably, in the preparation of grafted sodium lignin sulfonate, isopropanol is used in an appropriate amount to precipitate the grafted sodium lignin sulfonate.

[0035] More preferably, in the preparation of the sodium lignin sulfonate derivative, the grafted sodium lignin sulfonate is added to deionized water and mixed to obtain a grafted sodium lignin sulfonate solution, the pH is adjusted to 11-13, and then a derivatizing agent is added at 70-90° C. to react for 2-8 hours. After the reaction is completed, the solution is dialyzed in a dialysis bag for 1-5 days. After the dialysis treatment is completed, the solution is dried to obtain the sodium lignin sulfonate derivative.

[0036] More preferably, in the preparation of the sodium lignin sulfonate derivative, the amount of the grafted sodium lignin sulfonate used is 5-25 wt % of the deionized water.

[0037] More preferably, in the preparation of the sodium lignin sulfonate derivative, the derivatizing agent is diethyl chloromalonate, and the amount of the derivatizing agent used is 5-20 wt % of the grafted sodium lignin sulfonate.

[0038] More preferably, in the preparation of sodium lignin sulfonate derivatives, ethyl chloroethylcarbamate can also be added to the derivatizing agent, that is, the derivatizing agent is diethyl chloromalonate and ethyl chloroethylcarbamate, and the mass ratio of diethyl chloromalonate and ethyl chloroethylcarbamate in the derivatizing agent is 1:0.5-2. In the present invention, when preparing sodium lignin sulfonate derivatives, diethyl chloromalonate and ethyl chloroethylcarbamate are used as derivatizing agents in a specific ratio to prepare sodium lignin sulfonate derivatives, and after the sodium ion battery is made of the sodium lignin sulfonate derivatives as a binder, the rate performance, cycle stability and capacity retention rate of the sodium lignin sulfonate derivatives are improved.

[0039] The invention discloses a sodium ion battery prepared by the method.

[0040] The invention discloses a vehicle, comprising the sodium ion battery mentioned above.

[0041] The present invention ball-mills zirconium oxide ball mill beads and polycrystalline oxide positive electrode materials in a ball mill, then mixes with sodium carbonate for sintering, and then mixes with ammonium bicarbonate for sintering to prepare a sodium ion single crystal oxide positive electrode material, and then the sodium ion single crystal oxide positive electrode material and a binder are made into a homogenate in NMP, and then a positive electrode sheet is further prepared, and then a button-type half-battery is further prepared. When preparing the positive electrode sheet, the binder can use PVDF, sodium lignin sulfonate or sodium lignin sulfonate derivatives, so it has the following beneficial effects: the sodium ion single crystal oxide positive electrode material prepared by the present invention can improve the cycle performance and capacity performance of the sodium ion battery; the sodium ion battery prepared by the present invention has a high capacity retention rate and good cycle performance. Therefore, the present invention is a method for preparing a sodium ion single crystal oxide positive electrode material with a high capacity retention rate and good cycle performance after the battery is made. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is an electron microscope image of a polycrystalline oxide positive electrode material.

[0043] Figure 2 This is an electron microscope image of the polycrystalline oxide positive electrode material after ball milling.

[0044] Figure 3 This is an electron microscope image of the sodium ion single crystal oxide positive electrode material.

[0045] Figure 4 This is the capacity retention rate diagram of sodium ion battery. DETAILED DESCRIPTION

[0046] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] The following first describes the concepts involved in the present application in conjunction with the accompanying drawings. It should be noted that the following description of each concept is only to make the content of the present application easier to understand, and does not limit the scope of protection of the present application; at the same time, the embodiments and features in the embodiments of the present application can be combined with each other in the absence of conflict. The present application will be described in detail with reference to the accompanying drawings and in conjunction with the embodiments.

[0048] Example 1: A method for preparing a sodium ion single crystal oxide positive electrode material

[0049] Preparation of sodium ion single crystal oxide positive electrode material: put zirconium oxide ball milling beads and polycrystalline oxide positive electrode material into zirconium oxide ball milling jar, at a speed of 500 r / min, ball mill for 2h, wash with water, filter, dry to obtain intermediate product 1, mix intermediate product 1 with sodium carbonate, sinter at 800℃ for 8-16h in oxygen atmosphere, wash with water after cooling, filter, dry to obtain intermediate product 2, mix intermediate product 2 with ammonium bicarbonate, sinter at 800℃ for 10h in argon atmosphere, wash with water after cooling, filter, dry to obtain sodium ion single crystal oxide positive electrode material. Polycrystalline oxide positive electrode material is NaNi x Fe y Mn z O 2 , x+y+z=1, x=1 / 3, y=1 / 3; the ball-to-material ratio of zirconium oxide ball milling beads to polycrystalline oxide positive electrode materials is 15:1; the amount of intermediate product 1 used is measured based on the polycrystalline oxide positive electrode material, and the mass ratio of the amount of sodium carbonate used to the amount of polycrystalline oxide positive electrode material used is 1:1; the amount of intermediate product 2 used is measured based on the polycrystalline oxide positive electrode material, and the mass ratio of the amount of ammonium bicarbonate used to the amount of polycrystalline oxide positive electrode material used is 0.3:1.

[0050] Example 2: A method for preparing a sodium ion battery

[0051] Preparation of sodium ion battery: Add binder and sodium ion single crystal oxide positive electrode material to NMP and mix, homogenize at 1000rpm for 20min to obtain positive electrode slurry, and then make positive electrode plate; mix hard carbon material, carboxymethyl cellulose and acetylene black, homogenize at 1000rpm for 20min to obtain negative electrode slurry, and then make negative electrode plate; use polypropylene diaphragm as diaphragm, assemble the above positive electrode plate, negative electrode plate and electrolyte into button half-cell. The sodium ion single crystal oxide positive electrode material comes from Example 1, and the amount of sodium ion single crystal oxide positive electrode material used is 40wt% of NMP, the binder is PVDF, and the amount of binder used is 10wt% of the sodium ion single crystal oxide positive electrode material, and the sodium ion single crystal oxide positive electrode material loading on the positive electrode plate is 30mg·cm -2 ; The amount of carboxymethyl cellulose used is 5.5wt% of the hard carbon material, the amount of acetylene black used is 5.5wt% of the hard carbon material, and the hard carbon material loading on the negative electrode sheet is 30mg·cm -2 ; The electrolyte is NaPF 6 Solution, electrolyte is NaPF 6 , ethylene carbonate and diethyl carbonate, the electrolyte contains NaPF 6The concentration is 1M, and ethylene carbonate and diethyl carbonate are mixed in the electrolyte at a volume ratio of 1:1. The carrier of the positive electrode sheet is aluminum foil, and the carrier of the negative electrode sheet is copper foil.

[0052] Example 3: A method for preparing a sodium ion battery

[0053] Preparation of sodium ion battery: Add binder and sodium ion single crystal oxide positive electrode material to NMP and mix, homogenize at 1000rpm for 20min to obtain positive electrode slurry, and then make positive electrode sheet; mix hard carbon material, carboxymethyl cellulose and acetylene black, homogenize at 1000rpm for 20min to obtain negative electrode slurry, and then make negative electrode sheet; use polypropylene diaphragm as diaphragm, assemble the above positive electrode sheet, negative electrode sheet and electrolyte into button half-cell. The sodium ion single crystal oxide positive electrode material comes from Example 1, and the amount of sodium ion single crystal oxide positive electrode material used is 40wt% of NMP, the binder is sodium lignin sulfonate, and the amount of binder used is 10wt% of the sodium ion single crystal oxide positive electrode material, and the sodium ion single crystal oxide positive electrode material loading on the positive electrode sheet is 30mg·cm -2 ; The amount of carboxymethyl cellulose used is 5.5wt% of the hard carbon material, the amount of acetylene black used is 5.5wt% of the hard carbon material, and the hard carbon material loading on the negative electrode sheet is 30mg·cm -2 ; The electrolyte is NaPF 6 Solution, electrolyte is NaPF 6 , ethylene carbonate and diethyl carbonate, the electrolyte contains NaPF 6 The concentration is 1M, and ethylene carbonate and diethyl carbonate are mixed in the electrolyte at a volume ratio of 1:1. The carrier of the positive electrode sheet is aluminum foil, and the carrier of the negative electrode sheet is copper foil.

[0054] Example 4: A method for preparing a sodium ion battery

[0055] The difference between this embodiment and embodiment 3 is that in the preparation of the sodium ion battery, the binder in the preparation of the positive electrode sheet is replaced with a sodium lignin sulfonate derivative. The preparation of the sodium lignin sulfonate derivative includes the preparation of grafted sodium lignin sulfonate and the preparation of the sodium lignin sulfonate derivative.

[0056] Preparation of grafted sodium lignin sulfonate: Sodium lignin sulfonate is added to deionized water to obtain a sodium lignin sulfonate solution. Potassium persulfate is added and mixed at 50°C under an inert gas atmosphere. Ethoxyethoxyethyl acrylate is then added at 80°C to react for 2 hours. After the reaction is completed, isopropanol is added, and the precipitate is allowed to stand for precipitation. The precipitate is separated by filtration and dried to obtain grafted sodium lignin sulfonate. The amount of sodium lignin sulfonate used is 15wt% of deionized water, the amount of potassium persulfate used is 4wt% of sodium lignin sulfonate, the amount of ethoxyethoxyethyl acrylate used is 10wt% of sodium lignin sulfonate, and isopropanol is used in an appropriate amount to precipitate the grafted sodium lignin sulfonate.

[0057] Preparation of sodium lignin sulfonate derivatives: Grafted sodium lignin sulfonate is added to deionized water to obtain a grafted sodium lignin sulfonate solution, the pH is adjusted to 12, and then a derivatizing agent is added at 80°C for 4 hours. After the reaction is completed, the mixture is dialyzed in a dialysis bag for 3 days. After the dialysis treatment is completed, the mixture is dried to obtain a sodium lignin sulfonate derivative. The amount of grafted sodium lignin sulfonate used is 10wt% of deionized water, the derivatizing agent is diethyl chloromalonate, and the amount of the derivatizing agent used is 10wt% of the grafted sodium lignin sulfonate.

[0058] Example 5: A method for preparing a sodium ion battery

[0059] Compared with Example 4, this example is different in the preparation of grafted sodium lignin sulfonate and the preparation of sodium lignin sulfonate derivatives. In the preparation of grafted sodium lignin sulfonate, the amount of ethoxyethoxyethyl acrylate used is 12wt% of the sodium lignin sulfonate; in the preparation of sodium lignin sulfonate derivatives, the amount of the derivatizing agent used is 16wt% of the grafted sodium lignin sulfonate. Others are the same as Example 4.

[0060] Example 6: A method for preparing a sodium ion battery

[0061] Compared with Example 4, this embodiment is different in the preparation of sodium lignin sulfonate derivatives. In the preparation of sodium lignin sulfonate derivatives, the derivatizing agents are diethyl chloromalonate and ethyl chloroethylcarbamate, the mass ratio of diethyl chloromalonate to ethyl chloroethylcarbamate in the derivatizing agent is 1:0.8, and the amount of the derivatizing agent used is 10wt% of the grafted sodium lignin sulfonate.

[0062] Example 7: A method for preparing a sodium ion battery

[0063] The difference between this embodiment and embodiment 6 lies in the preparation of sodium lignin sulfonate derivatives. In the preparation of sodium lignin sulfonate derivatives, the amount of the derivatizing agent used is 15 wt % of the grafted sodium lignin sulfonate.

[0064] Comparative Example 1: A method for preparing a sodium ion battery

[0065] The difference between this comparative example and Example 2 is that the sodium ion single crystal oxide positive electrode material is replaced by a polycrystalline oxide positive electrode material, and the polycrystalline oxide positive electrode material is NaNi x Fe y Mn z O 2 , x+y+z=1, x=1 / 3, y=1 / 3.

[0066] Comparative Example 2: A method for preparing a sodium ion battery

[0067] This comparative example is different from Example 4 in that, in the preparation of grafted sodium lignin sulfonate, the amount of ethoxyethoxyethyl acrylate used is 2wt% of the sodium lignin sulfonate. In the preparation of sodium lignin sulfonate derivatives, the amount of the derivatizing agent used is 2wt% of the grafted sodium lignin sulfonate. Others are the same as Example 4.

[0068] Comparative Example 3: A method for preparing a sodium ion battery

[0069] This comparative example is different from Example 4 in that, in the preparation of grafted sodium lignin sulfonate, the amount of ethoxyethoxyethyl acrylate used is 2wt% of the sodium lignin sulfonate. In the preparation of the sodium lignin sulfonate derivative, the amount of the derivatizing agent used is 10wt% of the grafted sodium lignin sulfonate. Others are the same as Example 4.

[0070] Comparative Example 4: A method for preparing a sodium ion battery

[0071] This comparative example is different from Example 4 in that, in the preparation of grafted sodium lignin sulfonate, the amount of ethoxyethoxyethyl acrylate used is 10wt% of the sodium lignin sulfonate. In the preparation of the sodium lignin sulfonate derivative, the amount of the derivatizing agent used is 2wt% of the grafted sodium lignin sulfonate. Others are the same as Example 4.

[0072] Test example:

[0073] The present invention has carried out scanning electron microscopy characterization on the polycrystalline oxide positive electrode material in Example 1, and the result is as follows Figure 1 As shown, the polycrystalline oxide positive electrode material is in the form of large spherical particles.

[0074] The present invention has carried out scanning electron microscopy characterization on the polycrystalline oxide positive electrode material after ball milling in Example 1, and the result is as follows Figure 2 As shown, the polycrystalline oxide cathode material after ball milling is ground into small particles.

[0075] The present invention conducted a scanning electron microscope characterization on the sodium ion single crystal oxide positive electrode material prepared in Example 1, and the results were as follows: Figure 3 As shown, the sintered sodium ion single crystal oxide positive electrode material is in block form.

[0076] The present invention conducts constant current charge and discharge tests on the button-type half-cells prepared in the embodiments and comparative examples, with a voltage range of 1.5-4V, a current density of 1C, and a cycle number of 200. The capacity retention rate of the button-type half-cells prepared in the present invention is as follows: Figure 4 As shown, wherein S2 is Example 2, S3 is Example 3, S4 is Example 4, S5 is Example 5, S6 is Example 6, S7 is Example 7, D1 is Comparative Example 1, D2 is Comparative Example 2, D3 is Comparative Example 3, and D4 is Comparative Example 4. The present invention firstly ball-mills zirconium oxide ball mill beads and polycrystalline oxide positive electrode materials in a ball mill, and then mixes them with sodium carbonate for sintering, and then mixes them with ammonium bicarbonate for sintering to prepare a sodium ion single crystal oxide positive electrode material, and then prepares the sodium ion single crystal oxide positive electrode material and a binder in NMP. The slurry is then further prepared to obtain a positive electrode sheet, which is then further made into a button half-cell. When preparing the positive electrode sheet, the binder can use PVDF, sodium lignin sulfonate or a sodium lignin sulfonate derivative. In the present application, the capacity retention rate of the battery prepared using sodium lignin sulfonate is better than that of the battery prepared using PVDF. In order to further improve the performance of the battery, the present application modifies the sodium lignin sulfonate. When modifying the sodium lignin sulfonate, ethoxyethoxyethyl acrylate is first used to graft the sodium lignin sulfonate, and then diethyl chloromalonate is used as The derivatizing agent is used to derive the grafted sodium lignin sulfonate to obtain the sodium lignin sulfonate derivative. The capacity retention rate of the battery manufactured using the sodium lignin sulfonate derivative is better than that of the battery prepared using the sodium lignin sulfonate. When ethoxyethoxyethyl acrylate and diethyl chloromalonate are used, the usage amounts of ethoxyethoxyethyl acrylate and diethyl chloromalonate need to be within a suitable range. If the usage amount of ethoxyethoxyethyl acrylate or diethyl chloromalonate is small, and the usage amount of the other substance is within a suitable range, the capacity retention rate of the obtained battery is not as good as that of the battery manufactured using the sodium lignin sulfonate derivative. The capacity retention rate of the battery obtained within the appropriate range is high; when the usage amount of ethoxyethoxyethyl acrylate and diethyl chloromalonate is increased, the capacity retention rate of the battery obtained is also improved; ethyl chloroethylcarbamate can also be added to the derivatizing agent of the present invention, that is, diethyl chloromalonate and ethyl chloroethylcarbamate are used together as derivatizing agents to prepare sodium lignin sulfonate derivatives, and then the capacity retention rate of the battery prepared therefrom is improved, and when the usage amount of the derivatizing agent is further increased to prepare the sodium lignin sulfonate derivative, the capacity retention rate of the battery obtained is further improved.

[0077] The embodiments and / or implementation methods described above are only used to illustrate the preferred embodiments and / or implementation methods for realizing the technology of the present invention, and are not intended to limit the implementation methods of the technology of the present invention in any form. Any technical personnel in this field may make slight changes or modifications to other equivalent embodiments without departing from the scope of the technical means disclosed in the content of the present invention, but they should still be regarded as technologies or embodiments that are essentially the same as the present invention.

[0078] This article uses specific examples to illustrate the principles and implementation methods of this application. The description of the above embodiments is only used to help understand the method and its core ideas of this application. The above is only the preferred implementation method of this application. It should be pointed out that due to the limitations of textual expression and the objective existence of infinite specific structures, ordinary technicians in this technical field can make several improvements, modifications or changes without departing from the principles of this application, and can also combine the above technical features in an appropriate manner; these improvements, modifications, changes or combinations, or the direct application of the concept and technical solution of the invention to other occasions without improvement, should be regarded as the scope of protection of this application.

Claims

1. A method for preparing a sodium ion battery, comprising: The sodium ion single crystal oxide positive electrode material and the binder are mixed in a solvent, and the mixture is homogenized to prepare a positive electrode sheet for a sodium ion battery; Then, it is assembled with a sodium ion battery negative electrode sheet, a separator and an electrolyte to form a sodium ion battery; The preparation of the sodium ion single crystal oxide positive electrode material comprises: firstly ball milling the polycrystalline oxide positive electrode material, then mixing it with sodium carbonate and sintering it, and finally mixing it with ammonium bicarbonate and sintering it to obtain the sodium ion single crystal oxide positive electrode material; the mass ratio of the amount of sodium carbonate used to the amount of the polycrystalline oxide positive electrode material used is 0.5:1-2:1; the mass ratio of the amount of ammonium bicarbonate used to the amount of the polycrystalline oxide positive electrode material used is 0.1:1-0.5:1; the polycrystalline oxide positive electrode material is NaNi x Fe y Mn z O2, x+y+z=1, 0.2≤x<0.6, 0.2≤y<0.6; The binder is a sodium lignin sulfonate derivative, which has ethoxyethoxyethyl acrylate groups and diethyl chloromalonate groups; the amount of the binder used is 5-15wt% of the sodium ion single crystal oxide positive electrode material.

2. The method for preparing a sodium ion battery according to claim 1, characterized in that: In the ball milling treatment, zirconium oxide ball milling beads are used for ball milling, and the ball-to-material ratio of the zirconium oxide ball milling beads to the polycrystalline oxide positive electrode material is 15:1-20:

1.

3. The method for preparing a sodium ion battery according to claim 1, characterized in that: In the sintering treatment after mixing with sodium carbonate, sintering is performed at 700-900° C. in an oxygen atmosphere for 8-16 hours; or, in the sintering treatment after mixing with ammonium bicarbonate, sintering is performed at 600-850° C. in an argon atmosphere for 8-12 hours.

4. The method for preparing a sodium ion battery according to claim 1, characterized in that: The solvent is NMP; or, the amount of the sodium ion single crystal oxide positive electrode material used is 30-50wt% of the solvent.

5. A sodium ion battery prepared by the method according to any one of claims 1 to 4.

6. A vehicle comprising the sodium ion battery according to claim 5.

Citation Information

Patent Citations

  • Waste ternary positive electrode material single crystallization regeneration method

    CN113437377A